2020
DOI: 10.1101/2020.07.20.212258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemogenetic silencing of hippocampus and amygdala reveals a double dissociation in periadolescent obesogenic diet-induced memory alterations

Abstract: 1ABSTRACTIn addition to numerous metabolic comorbidities, obesity is associated with several adverse neurobiological outcomes, especially learning and memory alterations. Obesity prevalence is rising dramatically in youth and is persisting in adulthood. This is especially worrying since adolescence is a crucial period for the maturation of certain brain regions playing a central role in memory processes such as the hippocampus and the amygdala. We previously showed that periadolescent exposure to obesogenic hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…Our previous results show that 2-3 months of HFD intake, corresponding to the periadolescent period, has opposite effects on hippocampal and amygdala-dependent memory, impairing hippocampal-dependent spatial and relational memory (Boitard et al, 2012(Boitard et al, , 2014(Boitard et al, , 2016 but enhancing amygdala-dependent emotional memory (Boitard et al, 2015(Boitard et al, , 2016Naneix et al, 2020). Our BLA plasticity data fits with the emotional memory effect suggesting this could represent a cellular basis of the behavioural effect as we previously suggested (Boitard et al, 2015).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our previous results show that 2-3 months of HFD intake, corresponding to the periadolescent period, has opposite effects on hippocampal and amygdala-dependent memory, impairing hippocampal-dependent spatial and relational memory (Boitard et al, 2012(Boitard et al, , 2014(Boitard et al, , 2016 but enhancing amygdala-dependent emotional memory (Boitard et al, 2015(Boitard et al, , 2016Naneix et al, 2020). Our BLA plasticity data fits with the emotional memory effect suggesting this could represent a cellular basis of the behavioural effect as we previously suggested (Boitard et al, 2015).…”
Section: Introductionsupporting
confidence: 85%
“…During adolescence, the maturation of brain structures such as the hippocampus and the amygdala is crucial for cognitive and emotional functions (Andersen, 2003;Spear, 2000). We and others recently demonstrated that adolescent obesity, induced by post-weaning high-fat diet (HFD) consumption, impaired hippocampal-dependent spatial and relational memories in animal models (Boitard et al, 2012(Boitard et al, , 2014Khazen, Abu Hatoum, Ferreira, & Maroun, 2019;Valladolid-Acebes et al, 2013) whereas the same HFD exposure enhanced amygdala-dependent emotional memory (Boitard et al, 2015(Boitard et al, , 2016Naneix et al, 2020). This bidirectional effect of post-weaning HFD intake on hippocampal-and amygdala-dependent memory suggests cellular changes at the level of the hippocampus and the amygdala Mouna Maroun and Guillaume Ferreira contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we found that HFS diet impaired hippocampal-dependent memories when started in juveniles, but did not affect memory when started at adulthood [8], through aberrant ac6vity of the hippocampus [10,11]. Specifically, such memory impairments have been found to be associated with higher c-fos expression in the hippocampus and hippocampal efferent pathways to striatal and prefrontal areas [10,11] as well as aberrant synap6c transmission and plas6city in CA1 [12]. Interes6ngly, chemogene6c manipula6on of the hippocampus or its efferent pathways rescued memory deficits for object loca6on and long-term object recogni6on [11,13].…”
Section: Introduc5onmentioning
confidence: 71%
“…Our group has developed a model of juvenile HFS consump6on in rodents, from weaning to adulthood and showed that this paradigm induced memory deficits [8,9]. Importantly, we found that HFS diet impaired hippocampal-dependent memories when started in juveniles, but did not affect memory when started at adulthood [8], through aberrant ac6vity of the hippocampus [10,11]. Specifically, such memory impairments have been found to be associated with higher c-fos expression in the hippocampus and hippocampal efferent pathways to striatal and prefrontal areas [10,11] as well as aberrant synap6c transmission and plas6city in CA1 [12].…”
Section: Introduc5onmentioning
confidence: 80%
See 1 more Smart Citation